SELEÇÃO DE ISOLADOS DE BEAUVERIA BASSIANA, METARHIZIUM ANISOPLIAE E PAECILOMYCES FARINOSUS, PATOGÊNICOS PARA OPERÁRIAS DE ATTA SEXDENS SEXDENS (LINNAEUS, 1758) (HYMENOPTERA: FORMICIDAE) - Loureiro, E. De S. [UNESP]; Monteiro, A.c. [UNESP] (Instituto Biológico, 2024)
This study was carried out under laboratory conditions, aiming at the evaluation of the efficiency of enthomopathogenic fungi to control Atta sexdens sexdens. We utilized isolates of Beauveria bassiana (AM 9, JAB 06), Metarhizium anisopliae (E 9, AL), and Paecilomyces farinosus (CG 189, CG 195), inoculated on workers. After the collection, samples of workers were separated in groups of eight insects and baths with conidial suspension of 1.0 x 106, 1.0 x 107, 1.0 x 108 and 1,0 x 109 conidia/mL. Each group of ants was transferred to a moist chamber and maintained under starvation at 27 ± 1° C. The tree fungi were pathogenic, although P. farinosus (isolates CG 189 and CG 195) was the most virulent. This isolates were those ones that showed larger percentage of confirmed mortality. The most efficient concentration used in this study was 109 conidia/ mL, with LT50 of 1.48 days for isolate CG 189. Observing the mortality parameter on the third day after evaluation, the concentrations tested afforded the highest mortality (67.6%) and confirmed mortality of 96.05%. The isolates AM 9, E 9 and CG 189 promoted the highest mean mortalities for workers in the shortest time.

Este trabalho foi conduzido, em condições de laboratório, para se observar a eficiência de fungos entomopatogênicos no controle de Atta sexdens sexdens. Foram utilizados os isolados AM 9 e JAB 06 de Beauveria bassiana, E 9 e AL de Metarhizium anisopliae e CG 189 E CG 195 de Paecilomyces farinosus, inoculados em operárias. Após coleta, exemplares de operárias foram separados em grupos de 8 indivíduos e banhados em suspensões de conídios de 1,0 x 106 a 1,0 x 109 conídios/mL. Cada grupo de formiga foi transferido para câmara úmida e mantido sob regime de fome a 27 ± 1° C. Os três fungos foram patogênicos, embora P. farinosus (isolados CG 189 e CG 195) tenha sido o mais virulento dentre os testados. Esses isolados foram aqueles que apresentaram maior porcentagem de mortalidade confirmada. A concentração de 1,0 x 109 con./mL foi a mais eficiente, com TL50 de 1,48 dias para o isolado CG 189. Quanto ao parâmetro mortalidade, logo no 3o dia após a avaliação, as concentrações testadas proporcionaram alta porcentagem de operárias mortas (67,6%) e mortalidade confirmada de 96,05%. Os isolados AM 9, E 9 e CG 189 provocaram as maiores médias de mortalidade de operárias em menor espaço de tempo.
SELECTION OF BEAUVERIA BASSIANA, METARHIZIUM ANISOPLIAE AND PAECILOMYCES FARINOSUS ISOLATES, PATHOGENIC TO WORKERS OF ATTA SEXDENS SEXDENS (LINNAEUS, 1758) (HYMENOPTERA: FORMICIDAE)
Keywords: Leaf-cutting ant; biological control; microbiol control; entomopathogenic fungi; Saúva; formigas cortadeiras; controle biológico; controle microbiano; fungos entomopatogênicos